Community Development for Disaster Response in Volcanic Landscapes Based on Participatory Approach in Rua Village, Ternate City - Aji, Krishna; Tangge, Nurul Ainun; Ishak, Lily; Ladjinga, Erwin; Hartati, Tri Mulya; Robo, Sarif (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Landslides and flash floods are common natural disasters in volcanic landscapes. The repercussions of these events are substantial. A dearth of understanding, preparedness, and awareness of disaster risks can result in casualties, significant material losses, and impediments to the post-disaster recovery process. Disaster mitigation has been demonstrated to be an effective solution for managing post-disaster activities. The objective of this service activity is to elucidate the significance of participatory-based disaster mitigation in establishing a community that is responsive to disasters. The activity was carried out in Rua Village, Ternate Island District, Ternate City. The community service method employed is characterized by a socialization approach, encompassing mentoring, monitoring, and evaluation. Activities are carried out directly in the community in Rua Village. The findings of the initiative have contributed to an enhanced understanding of disaster mitigation strategies, particularly within the context of volcanic landscapes, in regions susceptible to such events. Additionally, the team emphasized the importance of implementing initiatives such as afforestation, erecting disaster-response shelters, and strengthening community resilience. Furthermore, additional coordination is necessary between the community and the local government to effectively manage disaster-prone areas. These regions must be identified as priorities so that the local government can implement initiatives aimed at cultivating disaster-resilient communities.